Situational Ethics Across Borders: A Multicultural Examination - Robertson, Christopher J. (Journal of business ethics, 2002)
Managers throughout the world regularly face ethical dilemmas that have important, and perhaps complex, professional and personal implications. Further, societal consequences of decisions made can be far-reaching. In this study, 210 financial services managers from Australia, Chile, Ecuador and the United States were queried about their ethical beliefs when faced with four diverse dilemmas. In addition, the situational context was altered so the respondent viewed each dilemma from a top management position and from a position of economic hardship. Results suggest a complex interaction of situation, culture and issue when individuals make ethical judgments. Specifically, Chileans were found to have different beliefs about sex discrimination and child labor dilemmas when compared to their colleagues from the other three nations. Chileans and Australians also disagreed on the bribery dilemma. Anglo managers were more likely than Latin American managers to change their ethical responses when the situation was altered. For multinational firms interested in maintaining healthy ethical climates, the findings suggest that culturally contingent ethical guidelines, or policies adapted to the local customs, must be considered. Further, managers must remain aware of issues related to specific situations, both internal and external, that would cause subordinates to alter their moral judgment.